Increased β-adrenergic inotropy in ventricular myocardium from Trpm4−/− mice - Mathar, Ilka; Kecskes, Miklos; Van der Mieren, Gerry; Jacobs, Griet; Camacho Londoño, Juan Eduardo; Uhl, Sebastian; Flockerzi, Veit; Voets, Thomas; Freichel, Marc; Nilius, Bernd; Herijgers, Paul; Vennekens, Rudi (Circulation research, 2014)
Rationale:The Trpm4 gene has recently been associated with several disorders, including cardiac conduction diseases and Brugada syndrome. Transient receptor potential member 4 (TRPM4) proteins constitute Ca2+-activated, but Ca2+-impermeable, nonselective cation channels and are expressed both in atrial and in ventricular cardiomyocytes. The physiological function of TRPM4 in the heart remains, however, incompletely understood.Objective:To establish the role of TRPM4 in cardiac muscle function.Methods and Results:We used TRPM4 knockout mice and performed patch-clamp experiments, membrane potential measurements, microfluorometry, contractility measurements, and in vivo pressure-volume loop analysis. We demonstrate that TRPM4 proteins are functionally present in mouse ventricular myocytes and are activated on Ca2+-induced Ca2+ release. In Trpm4−/− mice, cardiac muscle displays an increased β-adrenergic inotropic response both in vitro and in vivo. Measurements of action potential duration show a significantly decreased time for 50% and 90% repolarization in Trpm4−/− ventricular myocytes. We provide evidence that this change in action potential shape leads to an increased driving force for the L-type Ca2+ current during the action potential, which explains the altered contractility of the heart muscle.Conclusions:Our results show that functional TRPM4 proteins are novel determinants of the inotropic effect of β-adrenergic stimulation on the ventricular heart muscle.
Im Titel sind minus slash minus hochgestellt
Originally published 13 Nov 2013
Gesehen am 29.10.2020